Utilización de distintos niveles de triguillo y arrocillo en sustitución parcial del maíz en dietas para aves ponedoras de la raza Lohmann durante la etapa de levante de la semana 1 a la semana 8. - Chávez Valle, Jorge Vinicio (2022)
The objective of the present work was to evaluate two levels of wheat and rice in partial substitution of corn in diets for laying birds of the Lohmann breed during the rearing stage, in Avícola Plavalle of the Penipe canton, Chimborazo province. Under an experimental method, diets are supplied to 500 birds distributed with DCA, in the following treatments: control (T0), triguillo at 10% (TT10) and 20% (TT20), rice at 10% (TA10) and at 20 % (TA20). The nutritional requirements of the breed/age were met, proven by laboratory analysis. For data tabulation, an ADEVA with Bonferroni test was applied with p-value ≤0.05 at a significance level of 95%. Significant differences are reflected in the weights of weeks 4, 6 and 8 with better results for T0 (final weight 672.61 g/bird). In weight gain, there were no statistical differences between treatments until week 8, where T0 was better with 631.80 g of total gain.